Sex estimation from handprints in a Croatian population sample : developing a tool for sex identification in criminal investigations - Kolić, Andrea (Array, 2020)
To test if handprint measurements show sexual dimorphism in the Croatian population, and to develop population-specific sex estimation standards. Methods: A cross-sectional study was conducted on 100 adult volunteers from a Croatian population (50 males and 50 females) aged between 20 and 45 years. Using a fingerprint ink, we collected handprints of both hands on a paper sheet. We scanned handprints and took 13 measurements. Bilateral asymmetry and sexual dimorphism of the measurements was analyzed and sex estimation models were developed using linear discriminant analysis. Results: All measurements exhibited statistically significant sexual dimorphism (P<0.001). Univariate discriminant functions provided sexing accuracy from 75% to 92%. The highest accuracy rate (92%) and the lowest sexing bias (0%) was obtained using the handprint breadth. A multivariate discriminant function could estimate sex with 93% accuracy, but with more pronounced sexing bias (10%). Conclusion: We showed that handprint measurements could be used for sex estimation in the Croatian population with a high accuracy level. Therefore, they could serve as a valuable tool for biological profiling of perpetrators in criminal investigations when other evidence is not conclusive.